2021
DOI: 10.11646/palaeoentomology.4.4.14
|View full text |Cite
|
Sign up to set email alerts
|

The earliest record of fossil solid-wood-borer larvae—immature beetles in 99 million-year-old Myanmar amber

Abstract: Interactions between animals and plants represent an important driver of evolution. Especially the group Insecta has an enormous impact on plants, e.g., by consuming them. Among beetles, the larvae of different groups (Buprestidae, Cerambycidae, partly Eucnemidae) bore into wood and are therefore called wood-borer larvae or borers. While adults of these beetle groups are well known in the fossil record, there are barely any fossils of the corresponding larvae. We report here four new wood-borer larvae from Cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 76 publications
0
19
0
Order By: Relevance
“…Yet, this may be related to the fact that beetle larvae are much rarer reported than adults. Detailed search for such wood borer-type larvae reveals that they are indeed present in different ambers ( Haug et al, 2021b ; Zippel et al, 2022 ; Zippel et al., 2022b ; A Zippel, C Haug, P Müller & JT Haug, 2022, unpublished data). This may be seen as an argument that the new specimen might have been somehow wood-associated, but that could mean as well that the larva was scraping off algae from wood.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, this may be related to the fact that beetle larvae are much rarer reported than adults. Detailed search for such wood borer-type larvae reveals that they are indeed present in different ambers ( Haug et al, 2021b ; Zippel et al, 2022 ; Zippel et al., 2022b ; A Zippel, C Haug, P Müller & JT Haug, 2022, unpublished data). This may be seen as an argument that the new specimen might have been somehow wood-associated, but that could mean as well that the larva was scraping off algae from wood.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the larvae of extant species that affect crops while feeding have a substantial effect on humans directly, including larvae of Mordellidae, they are not as well represented in studies as one would expect (Liu et al 2018). The ratio of described larvae per number of known species is quite low compared to other groups of beetles and their relatives (see discussion in Haug et al 2021a). Due to the scarceness of data on larvae, the ecology of most tumbling flower beetle larvae remains unknown as well (Liu et al 2018).…”
Section: Introductionmentioning
confidence: 93%
“…He showed that similar morphologies also occur (due to convergent evolution) in certain larvae of jewel beetles (e.g., greBenniKov 2013: 167, fig. 1) which are known from few fossils (Haug et al 2021a), but also traces (ding et al 2014). Yet, in fact there is a third lineage of Holometabola with very similar-appearing larvae, Tenthredinidae, more specifically several species of birch-leafmining hymenopterans (e.g., Frost 1925, pl.…”
Section: Identity Of the New Caterpillarsmentioning
confidence: 99%
“…If taxonomic or phylogenetic interpretations of fossil specimens are challenging, these are often difficult to be included into measures of diversity over time. Morphological aspects of such animals offer an alternative objective measure of diversity, independent from a taxonomic frame (see Haug et al 2020bHaug et al , 2021aHaug et al , 2021bHaug et al , 2021cHaug et al , 2021d.…”
Section: Expanding the Diversity Of Cretaceous Caterpillarsmentioning
confidence: 99%